Convert sentences into First Order Logic

  • Thread starter Upeksha
  • Start date
  • #1
5
0
(1) Anyone who is thin, tall and energetic will be good basketball player.
(2) Some people are tall but not good basketball players.
(3) Anyone who do exercise or eating healthy food will be energetic.
(4) Saman is thin and tall person who do exercises.

Write the above sentences in First Order Logic.

I have tried like this:

(1) ∀x thin(x) ∧ tall(x) ∧ energetic(x) → good_basketball_player(x)
(2) ∃x tall(x) ¬ good_basketball_player(x)
(3) ∀x do_exercise(x) ∨ eating_healthy_food(x) → energetic(x)
(4) thin(saman) ∧ tall(saman) ∧ do_exercise(saman)
 

Answers and Replies

  • #2
TeethWhitener
Science Advisor
Gold Member
2,026
1,474
Some parentheses in the first three sentences would help to make it clear which part the quantifiers apply to. You're also missing a ∧ in #2.
 
  • #3
5
0
Thank you. Is it correct now?

(1) ∀x [thin(x) ∧ tall(x) ∧ energetic(x)] → good_basketball_player(x)
(2) ∃x [tall(x) ¬ good_basketball_player(x)]
(3) ∀x [do_exercise(x) ∨ eating_healthy_food(x)] → energetic(x)
(4) thin(saman) ∧ tall(saman) ∧ do_exercise(saman)
 
  • #4
TeethWhitener
Science Advisor
Gold Member
2,026
1,474
I'd probably put parentheses around the whole statement for 1 and 3. Otherwise you've got a situation where x is both a free and a bound variable.
 

Related Threads on Convert sentences into First Order Logic

Replies
10
Views
2K
Replies
35
Views
2K
  • Last Post
Replies
1
Views
2K
  • Last Post
Replies
3
Views
2K
  • Last Post
Replies
0
Views
153
  • Last Post
Replies
15
Views
3K
  • Last Post
Replies
6
Views
2K
  • Last Post
Replies
5
Views
680
Replies
2
Views
2K
Replies
0
Views
993
Top